A novel modulator of IL-6R prevents inflammation-induced preterm birth and improves newborn outcome - France Côté; Elizabeth Prairie; Estefania Marin Sierra; Christiane Quiniou; Tiffany Habelrih; Wendy Xu; Béatrice Ferri; Xin Hou; Isabelle Lahaie; Nadia Côté; Sarah-Eve Loiselle; Laurence Gobeil; et al. (EMBO Molecular Medicine)
Abstract Preterm birth (PTB) is a major cause of neonatal mortality and morbidity. Evidence supports a determinant role for interleukin-6 (IL-6) in the pathophysiology of PTB. Our group developed a small peptide, HSJ633, that antagonizes the interleukin-6 receptor (IL-6R). Binding assays performed on HEK-Blue IL-6 cells reveal that HSJ633 appears to bind to IL-6R on a site remote from the IL-6 binding domain. Concordantly, HSJ633 selectively inhibits STAT3 phosphorylation while preserving the activation of cytoprotective AKT, p38, and ERK 1/2. In vivo, in a murine model of LPS-induced PTB, HSJ633 reduces inflammation in gestational and fetal tissues, preserves the integrity of fetal organs, and improves the survival of neonatal progeny when administered before and after the induction of labor by an inflammatory stimulus. Relevantly, the pharmacological inhibition of STAT3 in mice is sufficient to prevent PTB. Findings reveal first-in-class efficacy of a small peptide inhibitor of IL-6R, namely HSJ633, in impeding the inflammatory cascade associated with PTB and mitigating adverse neonatal outcomes.